The presence of Saffron in Persian miniature paintings and its use as an inhibitor for the destructive effects of verdigris - Barkeshli, Mandana (1999)
The present study aims to investigate the possible reaction of green verdigris pigment mixed with saffron as a means of stopping the destructive effect of copper-based pigment, and to investigate the presence of saffron in green verdigris pigment and in Iran, as mentioned in Persian medieval texts. In order to examine the possible protective action of saffron, a major chemical mechanism responsible for this behavior- saffron solution serving as a buffer- has been studied and identified. The presence of saffron in green verdigris pigment has been also acknowledged by the FT-IR method. The result showed no indication 0f charring of paper on painted areas where verdigris pigment was mixed with saffron, whereas the verdigris used in pure form had extensively charred the paper support.